Benzoin type photoinitiator for free radical polymerization - Esen, Duygu Sevinc; Arsu, Nergis; Da Silva, Jose P.; Jockusch, Steffen; Turro, Nicholas J. (WILEY, 2013)
Benzoin, a popular photoinitiator for free radical polymerization of vinyl monomers, was improved by introduction of two methyl thioether substituents. This new benzoin derivative showed an about 50 times higher light absorption in the near-UV spectral region and performed better than the unsubstituted benzoin in polymerization experiments in bulk solutions or films of acrylate monomers when low initiator concentrations are used. Laser flash photolysis, low temperature luminescence experiments and photoproduct studies by mass spectrometry suggest that a slow -cleavage mechanism (k = 2.2 x 105 s1) from the electronic triplet state with a quantum yield of 0.1 is the primary photoreaction to generate the initiating free radicals. (c) 2013 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2013, 51, 1865-1871
Keywords: laser flash photolysis; photoinitiator; photopolymerization; photochemistry; photophysics; radical polymerization; PHOTOCHEMICAL ALPHA-CLEAVAGE; Polymer Science